A flume for assessing flux boundary characteristics in rainfall-induced slope failure studies - Rahardjo, Harianto (2011)
Rainfall-induced slope failure studies and slope hydrological behavior studies often require an assessment of the flux boundary characteristics of a slope. However, quantification of the flux boundary conditions across a slope surface with respect to rainfall, runoff, and infiltration is difficult. This paper introduces the design and field installation of a flume for high resolution monitoring of runoff data from a small catchment, particularly for rainfall-induced slope failure studies. The features of the flume include reliable and continuous runoff measurement at high resolution, options for accommodating various flow rates as dictated by the slope size, and portability. The flume can be used to quantify the flux boundary conditions required for seepage analyses associated with rainfall-induced slope failure studies.